Growth control of listeria innocua 2030c on vacuum-packaged cold-smoked salmon by lactic acid bacteria - Tomé, Elisabetta (2010)
Five bacteriocin-producing lactic acid bacteria (LAB): Enterococcus faecium ET05, Lactobacillus curvatus ET06, L. curvatus ET30, L. deldrueckii ET32 and Pediococcus acidilactici ET34, selected by their capacity for growth and producing inhibition in vitro at high salt-on-water content, low temperature and anaerobic atmosphere, conditions simulating cold-smoked fish,were inoculated onto salmon fillets, in co-culturewith Listeria innocua 2030c, and cold-smoked processed (dry salted for 6h; drying for 6h; smoke for 2h).The finished product was then packed under vacuum and stored at 5 °C. Enumeration of LAB and L. innocua was performed during storage. Results showed that strain E. faecium ET05 was the best biopreservative candidate for controlling L. innocua growth in vacuum-packaged cold-smoked salmon (CSS) processed under the salting/drying/smoking parameters referred above. L. curvatus ET30 and L. delbrueckii ET32 also showed a good biopreservation potential for CSS although they were less effective than the former. L. curvatus ET06 and P. acidilactici ET34 showed a bacteriostatic mode of action against the target bacteria in vitro as well as when inoculated into the salmon fillets. This study describes a potential application of five different LAB in the biopreservation of Listeria in CSS.